Effect of clay surface on aldehyde-diol equilibrium. Issue 36 (5th September 2019) - Arakawa, Kyosuke; Nakazato, Ryosuke; Shimada, Tetsuya; Ishida, Tamao; Eguchi, Miharu; Takagi, Shinsuke
Graphical abstract: Equilibrium on the flat surface. Highlights: The effect of flat clay surface on the equilibrium between aldehyde and diol was examined. 4-Formyl-1-methylpyridin-1-ium was clearly observed in the presence of clay nanosheet even in water. Flat clay nanosheet surface modulate the potential energy curve of equilibrium. Abstract: The effect of clay surface on the equilibrium between aldehyde and diol was examined by using 4-formyl-1-methylpyridin-1-ium chloride (MPy + ) as a substrate. MPy + exists as diol (DHMPy + ) and aldehyde (FMPy + ) in water and acetonitrile, respectively. It was turned out that FMPy + was clearly observed in the presence of clay nanosheet even in water. This indicates that clay nanosheet surface acts as unique chemical reaction field, affecting the potential energy surface between FMPy + and DHMPy + .